Pengaruh Permainan Ular Tangga Huruf Hijaiyah Terhadap Kemampuan Mengenal Huruf Hijaiyah Anak Usia 4-5 Tahun - Zabid Latifah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the effect of the snake ladder game of hijayah letters on theability to recognize hijayah letters of children aged 4-5 years in RA Perwanida GrabagGrabag District Magelang Regency.This research is a quasi-experimental research. Thevariables used in this study were the game of snakes and ladders hijaiyah letters as theindependent variable and the ability to recognize hijaiyah letters for children aged 4-5years as the dependent variable. The population in this study were all students of group Ain RA Perwanida Grabag totaling 90 children. The sampling technique used saturatedsampling technique, so that a sample of all students in group A RA Perwanida Grabag,totaling 90 children, was divided into two groups, 46 as the experimental group and 44 asthe control group. Methods of data collection using observation techniques. The dataanalysis technique used statistical non parametric Mann Whitney test.The results of thestudy concluded that the game of snakes and ladders hijaiyah letters had a positive effecton the ability to recognize hijaiyah letters for children aged 4-5 years. This is evidenced bythe acquisition of the Mann Whitney test value with a calculated z value of -5.947 with aprobability value of 0.000 < 0.05. The results of the study can be concluded that the gameof snakes and ladders hijaiyah letters affects the ability to recognize hijaiyah letters forchildren aged 4-5 years.